Mesoscale flow and heat transfer modelling and its application to liquid and gas flows - Asproulis, Nikolaos; Kalweit, Marco; Shapiro, Evgeniy; Drikakis, Dimitris (Cranfield University, 2009)
Advances in micro and nanofluidics have influenced technological developments in several areas, including materials, chemistry, electronics and bio-medicine. The phenomena observed at micro and nanoscale are characterised by their inherent multiscale nature. Accurate numerical modelling of these phenomena is the cornerstone for enhancing the applicability of micro and nanofluidics in the industrial environment. We investigated different strategies for applying macroscopic boundary conditions to microscopic simulations. Continuous rescaling of atomic velocities and velocity distribution functions, such as Maxwell-Boltzmann or Chapman-Enskog, were investigated. Simulations were performed for problems involving liquids and gases under different velocity and temperature conditions. The results revealed that the selection of the most suitable method is not a trivial issue and depends on the nature of the problem, availability of computational resource and accuracy requirement.
Keywords: multiscale modelling heat transfer molecular dynamics hybrid atomistic continuum methods micro/nanofluid dynamics molecular-dynamics simulation continuum simulations fluid particle microscale roughness